Doppelganger - Klein, Naomi, 1970- (New York, N.Y. : Farrar, Straus and Giroux, 2023)
"What if you woke up one morning and found youd acquired another self--a double who was almost you and yet not you at all? What if that double shared many of your preoccupations but, in a twisted, upside-down way, furthered the very causes youd devoted your life to fighting against? Not long ago, the ... activist and public intellectual Naomi Klein had just such an experience: she was confronted with a doppelganger whose views she found abhorrent but whose name and public persona were sufficiently similar to her own that many people got confused about who was who. Destabilized, she lost her bearings, until she began to understand the experience as one manifestation of a strangeness many of us have come to know but struggle to define: AI-generated text is blurring the line between genuine and spurious communication; New Age wellness entrepreneurs turned anti- vaxxers are scrambling familiar political allegiances of left and right; and liberal democracies are teetering on the edge of absurdist authoritarianism, even as the oceans rise"--
Keywords: Klein, Naomi, -- 1970-; Influence; Psychological aspects; Political aspects; Internet -- Moral and ethical aspects; Conservatism -- Psychological aspects; Conservatism -- Social aspects